2017
DOI: 10.1002/ange.201708505
|View full text |Cite
|
Sign up to set email alerts
|

Fluorine Effects on Group Migration via a Rhodium(V) Nitrenoid Intermediate

Abstract: An unprecedented rhodium(III)-catalyzed hydroarylation of a,a-difluoromethylene alkynes with N-pivaloxyl aroylamides through sequential CÀHa ctivation and aryl migration is detailed herein. Al arge arrayo fa,a-difluoromethylene alkynes and N-pivaloxyl aryl amides were amenable to this transformation, thus providing an ovel synthetic protocol for the construction of difluorinated 2-alkenyl aniline derivatives in high yields and with excellent regioselectivity. Notably,unique fluorine effects were found to under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 78 publications
1
2
0
Order By: Relevance
“…This result indicated that pathway Bmight be more favorable, and is also consistent with previous reports by the groups of Feng [12] and Tanaka. This result indicated that pathway Bmight be more favorable, and is also consistent with previous reports by the groups of Feng [12] and Tanaka.…”
supporting
confidence: 92%
“…This result indicated that pathway Bmight be more favorable, and is also consistent with previous reports by the groups of Feng [12] and Tanaka. This result indicated that pathway Bmight be more favorable, and is also consistent with previous reports by the groups of Feng [12] and Tanaka.…”
supporting
confidence: 92%
“…To determine the order of the Lossen rearrangement and the carbene migratory insertion, 1na was subjected to the standard reaction condition with several nucleophiles such as methanol and aniline instead of 2a,which, however, resulted in no Lossen rearrangement/nucleophilic addition product, but only in recovery of the starting materials (Scheme 5E). This result indicated that pathway Bmight be more favorable, and is also consistent with previous reports by the groups of Feng [12] and Tanaka. [10d] Based on the experimental results,atentative mechanism for the reaction is proposed (Scheme 6).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…In recent years, the −NHOR-tethered substrate has also been found to proceed with an unusual Lossen rearrangement triggered by a rhodium-catalyzed C–H activation . In 2017, Feng’s group disclosed a Rh­(III)-catalyzed C–H activation/Lossen rearrangement of N -pivaloyloxybenzamides with internal alkynes to afford alkenylation products . Thereafter, Rh­(III)-catalyzed C–H activation/Lossen rearrangement/[3 + 2] annulation and [4 + 2] annulation cascades (Scheme c) were independently developed by Tanaka and Osipov et al ., providing highly functionalized indole- and quinolone-containing amino acid derivatives.…”
mentioning
confidence: 99%